2016
DOI: 10.1515/bhk-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Blood ammonia and lactate responses to incremental exercise in highly-trained male sprinters and triathletes

Abstract: SummaryStudy aim: To compare the blood ammonia and lactate concentrations in sprinters and triathletes during an incremental treadmill exercise test and in the 30 minutes of recovery. Material and methods:The study included 10 male sprinters and 14 male triathletes who compete at the national and international level. A treadmill test until exhaustion was administered. Blood samples for ammonia and lactate were obtained when the athletes were at rest, during and immediately after exercise, and between 5 and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The source of bioactivity in EMW is thought to involve the presence of charge-stabilized nanostructures (CSNs), which by virtue of their size, charge, and stability affect constituents of the cell membrane [35, 36]. During exercise, increased lactate levels in exercising muscle and blood may trigger sensations of pain and discomfort, thus elevating perceptions of exertion [20, 37]. Ammonia is fatigue factor, whereby reduction of blood ammonia could prevent muscle catabolism and muscle damage [20].…”
Section: Discussionmentioning
confidence: 99%
“…The source of bioactivity in EMW is thought to involve the presence of charge-stabilized nanostructures (CSNs), which by virtue of their size, charge, and stability affect constituents of the cell membrane [35, 36]. During exercise, increased lactate levels in exercising muscle and blood may trigger sensations of pain and discomfort, thus elevating perceptions of exertion [20, 37]. Ammonia is fatigue factor, whereby reduction of blood ammonia could prevent muscle catabolism and muscle damage [20].…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al suggested that the highest blood lactate levels were observed after the first trial set, they decreased significantly toward the second trial set, and were maintained at the same level after the third trial set (Takagi et al, 2013). Also, Kantanista et al (Kantanista et al, 2016) found that exercise increases blood lactate.…”
Section: Discussionmentioning
confidence: 97%
“…This data was in line with the findings of Degoutte et al (Degoutte et al, 2003), who observed that lactate concentrations in blood were appeared to return to the baseline level within 24 hours. Also, in study conducted by Kantanista blood lactate decreased after the interruption of exercise (Kantanista et al, 2016). Adversely, Jafari et al suggested that the blood lactate significantly increased 24 hours after 1600 meter running among 27 non athlete boys (Jafari et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…AMP is deaminated to inosine monophosphate (IMP) and ammonia via the enzyme AMP deaminase [10]. Ammonia accumulation in blood has been observed in endurance athletes and exercise-related increase in blood ammonia is almost linear, regardless of the exercise intensity [16]. In previous studies, lower ammonia accumulation has been observed in endurance athletes [9].…”
Section: Discussionmentioning
confidence: 99%